Socio-demographic Characteristics and Dietary Habits of Individuals Who Refer to Guidelines for Food and Nutrition - Akamatsu, Rie; Ito, Nana (Eiyōgaku zasshi, 2015)
Objective: To compare the socio-demographic characteristics and dietary habits between individuals who refer to guidelines for food and nutrition and these who do not, for the preparation of nutrition education material. Methods: Data from the study “Research about the present status of and consciousness about shokuiku” conducted by the Cabinet Office between November and December 2009 were used. Based on the responses to the question “Do you refer to guidelines for food and nutrition?”, the subjects were divided into the Reference (subjects who refer to at least one of five guidelines) and Non-reference groups (subjects who did not refer to the guidelines). We compared the socio- demographic characteristics and dietary habits of the two groups using chi-square test and single variable logistic regression analyses. Results: Of the 2,936 participants, data of 2,699 subjects (91.9%) were analyzed: 1,338 (49.6%) in the Reference group and, 1,361 (50.4%) in the Non-reference group. The Japanese Food Guide Spinning Top was the most frequently referenced dietary guide [158(11.8%)]. The number of women (p<0.001) and subjects aged ≧60 years (p = 0.001) was significantly higher in the Reference group than in the Non-reference group. Additionally, more subjects in the Reference group ate breakfast (odds ratio [OR] = 1.35, 95% confidence interval [CI] = 1.04~1.77), and balanced meals (OR = 1.48, 95%CI = 1.22~1.80) . Conclusion: The socio-demographic characteristics of the two groups were different. Compared to the subjects in the Non-reference group, fewer subjects in the Reference group skipped meals, and a higher number ate balanced meals and vegetable dishes.